Pengaruh Relationship Marketing dan Customer Value Terhadap Loyalitas Pelanggan Indihome Pada PT Telkom Indonesia di Kota Sorong - Susetyowati Sofia; Nafisah Nur Zafitri Ashar; Agilistya Rahayu (Journal of Economics and Management (JECMA), 2023)
This study aims to determine how much influence Marketing Relationships and Customer Value have on Customer Loyalty. The method used in this research is the correlation method with a quantitative approach. The population in this study were customers of Indihome PT.Telkom Indonesia in Sorong City in March 2022, totaling 326 people. Sampling technique using random sampling method. The results of the study are 1), there is an influence of Relationship Marketing on Indihome Customer Loyalty PT.Telkom Indonesia Sorong City 2) there is an influence of Customer Value on Indihome Customer Loyalty PT.Telkom Indonesia Sorong City, 3) there is an effect of Relationship Marketing and Customer Value on Indihome Customer Loyalty PT. Telkom Indonesia, Sorong City